MODEL LINK AND MATCH PENDIDIKAN VOKASI DAN DAMPAKNYA TERHADAP PASAR TENAGA KERJA: A SYSTEMATIC LITERATURE REVIEW PADA SEKOLAH MENENGAH KEJURUAN DI INDONESIA - Muhammad Guntur Setyawan; Mulia Siti Kartika; Nina Farliana; Rania Safira; Wanadya Dwi Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was prompted by the high unemployment rate among vocational high school (SMK) graduates in Indonesia, which exceeds 8%. This is due to a mismatch between their skills and the industry's needs. This highlights the urgent need to strengthen 'link and match' policies to bridge the gap between the education sector and the workforce. This study aims to identify and analyse the impact of link-and-match models on labour market indicators, and to examine the factors that support or hinder their implementation in SMKs in Indonesia. A Systematic Literature Review (SLR) was conducted using the PSALSAR framework (Protocol, Search, Appraisal, Literature Synthesis, Analysis, Synthesis, and Report). The results suggest that implementing the link-and-match model through curriculum alignment, industry partnerships, and practice-based learning could reduce competency gaps. However, the effectiveness of this approach is hindered by limited facilities, insufficient human resource readiness, and weak sectoral collaboration. This study makes a theoretical contribution to the development of a holistic vocational education model and serves as a policy reference for the government in its vocational high school revitalisation programme. Strong synergy between schools and industry is key to enhancing competitiveness and graduate employability in the labour market.